cos (45 + x) + cos (x + 315) = sqrt(2)cos(x)
(Side note: 45 degrees = pi/4)
(315 degrees = 7pi/4)
Whenever solving identities, you choose either the left hand side (LHS) or the right hand side (RHS). The best one to choose is the more complex side, and in this case it's the LHS.
LHS = cos (45 + x) + cos (x + 315)
Remember the cosine addition identity:
cos(a + b) = cos(a)cos(b) - sin(a)sin(b)
This is what we apply.
LHS = [cos(45)cos(x) - sin(45)sin(x)] + [cos(x)cos(315) - sin(x)sin(315)]
Since those are familiar values on the unit circle, we can evaluate them directly.
LHS = [sqrt(2)/2]cos(x) - [sqrt(2)/2]sin(x) + cos(x)[sqrt(2)/2] -
sin(x)[-sqrt(2)/2]
Simplifying this a bit more and doing a bit of rearranging, we have
LHS = [sqrt(2)/2]cos(x) - [sqrt(2)/2]sin(x) + [sqrt(2)/2]cos(x)
+ [sqrt(2)/2]sin(x)
{Note: the minus sign in front of the last sqrt(2)/2 merged with the minus sign on the outside to form a plus}.
Notice that the second and fourth terms cancel each other out (one being a plus, the other being a minus, and them being exactly the same).
LHS = [sqrt(2)/2]cos(x) + [sqrt(2)/2]cos(x)
Also notice that these two terms are exactly the same, and we have two of them.
LHS = 2 [sqrt(2)/2]cos(x)
Now, notice the 2 cancels out with the 2 on the denominator, and our result is equal to the right hand side.
LHS = [sqrt(2)]cos(x) = RHS
2006-12-26 03:58:42
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Let's use the addition formula for the cosine:
cos(a + b) = cos a cos b - sin a sin b
which easily implies
cos(a - b) = cos a cos b + sin a sin b.
Now note that
cos(360 - x) = cos 360 cos x + sin 360 sin x = cos x
cos(x + 315)= cos(360-(315 + x)) = cos(45 -x)
To finish the job we have
cos(45 +x) = cos 45 cos x - sin 45 sin x
cos(45 -x) = cos 45 cos x + sin 45 sin x.
Adding these, we get
2cos 45 cos x = sqrt(2)*cos x.
Hope that helps!
2006-12-26 12:07:26
·
answer #2
·
answered by steiner1745 7
·
0⤊
0⤋
dear tink
just make use twice of the formule
cos ( a+b) = cos a cos b - sen a sen b and remembering
2 cos 45 = 2 cos 315 = root of 2, will get what you wish.
2006-12-26 11:55:31
·
answer #3
·
answered by ptolemy 1
·
0⤊
0⤋
cos(45+x)+cos(x+315)=RHS
LHS=
cos45cosx-sin45sinx
+
cosxcos315-sinxsin315
remember cos315=cos(-45)=cos45
sin315=sin(-45)= - sin45
Hence
LHS=cos45cosx-sin45sinx
+
cosx. cos45+sinx. sin45
=2cosxcos45 + 0
=2 root(2)/2 .cosx
=root(2). cosx
=RHS
2006-12-26 12:14:38
·
answer #4
·
answered by iyiogrenci 6
·
0⤊
0⤋
cos(45+x) + cos(x+315)
= cos(45+x) + cos(x-45)
= 2cos(45)cos x
=â2 cos x
2006-12-26 11:52:30
·
answer #5
·
answered by sahsjing 7
·
1⤊
0⤋
Can you add additional details? The question is truncated so maybe you can write it in pieces so someone can help you.
>> sahsjing's proof works
2006-12-26 11:52:44
·
answer #6
·
answered by Professor Maddie 4
·
0⤊
0⤋
Just a plumber next have a HAPPY NEW YEAR
2006-12-26 11:49:12
·
answer #7
·
answered by LVTHEPLUMBER 2
·
0⤊
3⤋
no.
2006-12-26 11:48:17
·
answer #8
·
answered by texas 2
·
0⤊
3⤋